Comparison of Maintenance in Different Materials for Implant Dental Prostheses - Neelam Suman; Niharika Munuganti; Sareen Duseja; Hina Naim Abdul; Rahul Puthenkandathil; Kishan K. Choithani; Ashok Kumar; Vilas Patel; Sirisha Kommuri (Wolters Kluwer Medknow Publications, 2024)
Context: In contemporary prosthodontics, implant-supported dental prostheses are frequently utilized to restore function and esthetics for individuals who are edentulous. The prosthetic material selection has a big impact on long-term performance and maintenance needs. Methods: A retrospective review of patient files from the dental implant clinic of a tertiary care facility was done. Included were patients who had dental prosthesis supported by implants between January 2018 and December 2022. Data were gathered and examined on the prosthesis material, follow-up visits, and maintenance interventions (adjustments, repairs, and replacements). Results: Materials for 50 prostheses made of porcelain, 45 prostheses made of acrylic, 35 prostheses made of metal, and 40 prostheses made of composite were assessed. When it came to modifications and repairs, porcelain prosthesis needed less work than acrylic prostheses. Composite prostheses required the least amount of maintenance overall, whereas metal prostheses indicated a considerable demand for maintenance. Conclusion: Superior durability is provided by porcelain, frequent repairs are needed for acrylic, structural strength is provided by metal, and composite material gives promising esthetics with low maintenance requirements. These results highlight how crucial it is to take material properties into account when choosing a prosthesis to maximize long-term results and patient happiness.